Chemical Composition, Enantiomeric Distribution and Antimicrobial, Antioxidant and Antienzymatic Activities of Essential Oil from Leaves of Citrus x limonia - Eduardo Valarezo; Laura Toledo-Ruiz; Wolter Coque-Saetama; Alfredo Caraguay-Martínez; Ximena Jaramillo-Fierro; Nixon Cumbicus; Miguel Angel Meneses (Molecules)
Citrus x limonia is an aromatic species belonging to the Rutaceae family. In the present study, the chemical composition, enantiomeric distribution, and biological activity of the essential oil isolated from leaves of Citrus x limonia were determined. The essential oil was extracted through hydrodistillation. The chemical composition of the essential oil was determined by gas chromatography (GC) coupled to a flame ionization detector (GC-FID), and a mass spectrometer detector (GC-MS) using a nonpolar column. The enantiomeric distribution was performed using two enantioselective chromatographic columns. Antimicrobial activity was determined using the broth microdilution method. The antimicrobial activity was tested against eight bacteria and two fungi. The antioxidant activity was determined through ABTS and DPPH methods. The spectrophotometric method was used to determine anticholinesterase activity. In the essential oil, forty-three compounds were identified. These compounds represent 99.13% of the total composition. Monoterpene hydrocarbons were the most representative group in number of compounds (fourteen) and in terms of relative abundance (65.67%). The main constituent is found to be limonene (25.37 ± 0.80%), β-pinene (23.29 ± 0.15%) and sabinene (8.35 ± 0.10%). Six pairs of enantiomers were identified in the essential oil from fruits of Citrus x limonia. The essential oil showed moderate antibacterial activity against Gram-positive cocci Enterococcus faecalis, and Gram-positive bacillus Lysteria monocytogenes with a MIC of 1000 μg/mL. The oil exhibited strong antifungal activity against fungi Aspergillus niger, and yeasts Candida albicans with a MIC of 250 and 500 μg/mL, respectively. The antioxidant activity of essential oil was weak in ABTS method with a SC50 of 9.12 mg/mL. Additionally, the essential oil presented moderate anticholinesterase activity with an IC50 of 71.02 ± 1.02 µg/mL.